Optimizing Seaweed (Ascophyllum nodosum) Thermal Pyrolysis for Environmental Sustainability: A Response Surface Methodology Approach and Analysis of Bio-Oil Properties - Zahidul Islam Rony; Mohammad Golam Rasul; Md Islam Jahirul; Mohammad Mehedi Hasan (Energies, 2024)
This study focuses on optimizing the thermal pyrolysis process to maximize pyrolysis oil yield using marine biomass or seaweed. The process, conducted in a batch reactor, was optimized using response surface methodology and Box–Behnken design. Variables like temperature, residence time, and stirring speed were adjusted to maximize bio-oil yield. The optimal conditions yielded 42.94% bio-oil at 463.13 °C, with a residence time of 65.75 min and stirring speed of 9.74 rpm. The analysis showed that temperature is the most critical factor for maximizing yield. The bio-oil produced contains 11 functional groups, primarily phenol, aromatics, and alcohol. Its high viscosity and water content make it unsuitable for engines but suitable for other applications like boilers and chemical additives. It is recommended to explore the potential of refining the bio-oil to reduce its viscosity and water content, making it more suitable for broader applications, including in engine fuels. Further research could also investigate the environmental impact and economic feasibility of scaling up this process.